Proteomics analysis of cancer tissues identifies IGF2R as a potential therapeutic target in laryngeal carcinoma - Liu, Bing; Hu, Yuqiang; Wan, Lixia; Wang, Luan; Cheng, Liangjun; Sun, Hai; Liu, Yaran; Wu, Di; Zhu, Jiefei; Hong, Xiu; Li, Yang; Zhou, Chong (Frontiers in Endocrinology, 2022)
Background: Laryngeal cancer (LC) is a prevalent head and neck malignancy; however, the essential pathophysiological mechanism underlying its tumorigenesis and progression remains elusive. Due to the perduring scarcity of effective targeted drugs for laryngeal cancer, insights into the disease’s pathophysiological mechanisms would substantially impact the treatment landscape of laryngeal cancer. Methods: To ensure quality consistency, 10 tumor and 9 non-tumor samples underwent proteomic analysis on a single mass spectrometer using a label-free technique. Subsequently, gene expression variations between laryngeal squamous cell carcinoma and normal tissues were analyzed using The Cancer Genome Atlas (TCGA) database. Immunohistochemical expressions of insulin-like growth factor 2 receptor (IGF2R), fibronectin (FN), vimentin, and α-smooth muscle actin (SMA) in LC tissues and normal tissues were determined. Results: In the tumor group, significant variations were detected for 433 upregulated and 61 downregulated proteins. Moreover, the heatmap revealed that the expressions of RNA translation-related proteins and proteins involved in RNA metabolism, such as IGF2R, tenascin C (TNC), periostin (POSTN), proteasome 26S subunit ATPase 4 (PSMC4), serpin family A member 3 (SERPINA3), heat shock protein family B (small) member 6 (HSPB6), osteoglycin (OGN), chaperonin containing TCP1 subunit 6A (CCT6A), and chaperonin containing TCP1 subunit 6B (CCT6B), were prominently elevated in the tumor group. Nonsense-mediated RNA decay (NMD), RNA translation, and protein stability were significantly altered in LC tumors. IGF2R was remarkably upregulated in LC tumors. In the TCGA database, the IGF2R mRNA level was significantly upregulated in LSCC tissues. Additionally, IGF2R mRNA expression was lowest in clinical grade 1 samples, with no significant difference between grades 2 and 3. In LSCC patients, a significant positive correlation between IGF2R expression and the stromal score was detected using the ESTIMATE algorithm to estimate the immune score, stromal score, and tumor purity in the tumor microenvironment. Lastly, immunohistochemical analysis revealed that IGF2R is overexpressed in LC. Conclusion: These results demonstrate the vital role of IGF2R in LC carcinogenesis and progression and may facilitate the identification of new therapeutic targets for the prevention and treatment of LC.